2020
DOI: 10.1002/aur.2311
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Screen of Mid‐pregnancy Maternal Serum and Autism in Offspring

Abstract: Discovering pathophysiologic networks in a blood‐based approach may help to generate valuable tools for early treatment or preventive measures in autism. To date targeted or untargeted metabolomics approaches to identify metabolic features and pathways affecting fetal neurodevelopment have rarely been applied to pregnancy samples, that is, an early period potentially relevant for the development of autism spectrum disorders (ASD). We conducted a population‐based study relying on autism diagnoses retrieved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…For example, one could imagine two metabolites that have the same concentrations in TD and ASD, but whose correlation changes with age or other conditions (e.g, diet; example [ 48 ]). Much of the literature on biomarkers of ASD and/or IDD has focused on the search for individual molecules, or statistical combinations of molecules, which are predictive of ASD-related morbidity or diagnosis [ 16 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, few metabolomic studies have moved beyond individual, isolated biomarkers, focusing instead on metabolic pathway analysis, in which whole metabolic pathways are analyzed for significant changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one could imagine two metabolites that have the same concentrations in TD and ASD, but whose correlation changes with age or other conditions (e.g, diet; example [ 48 ]). Much of the literature on biomarkers of ASD and/or IDD has focused on the search for individual molecules, or statistical combinations of molecules, which are predictive of ASD-related morbidity or diagnosis [ 16 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, few metabolomic studies have moved beyond individual, isolated biomarkers, focusing instead on metabolic pathway analysis, in which whole metabolic pathways are analyzed for significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, few metabolomic studies have moved beyond individual, isolated biomarkers, focusing instead on metabolic pathway analysis, in which whole metabolic pathways are analyzed for significant changes. To cite a few examples, at the prenatal level, Ritz et al [ 16 ] showed differences in several metabolic pathways, including glycosphingolipid biosynthesis and metabolism, N -glycan and pyrimidine metabolism, bile acid pathways and, importantly, C21-steroid hormone biosynthesis and metabolism in maternal mid-pregnancy serum samples from women residing in California and whose children later developed ASD. Nolin et al [ 88 ] reported deficits in the serine biosynthetic pathway as a main source of anaplerosis for the Krebs’ cycle in amniotic fluids from women carrying a fetus with a FMR1 premutation vs. noncarriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to that study, further research has found that combining low maternal high-density lipoprotein cholesterol along with high maternal plasma branched-chain amino acid levels and the child being male led to an increased risk of the child being diagnosed with ASD (36). Another study involving maternal metabolite levels prepregnancy from blood samples stored from that time, found that mothers who had children with ASD showed differences in several metabolic pathways including bile acid pathways, glycosphingolipid synthesis, N-glycan and pyrimidine metabolism, and C21-steroid hormone biosynthesis and metabolism (37).…”
Section: Implication On Possible Role Of Nutritional/metabolic Statusmentioning
confidence: 99%
“…Similar to that study, further research has found that combining low maternal high-density lipoprotein cholesterol along with high maternal plasma branched-chain amino acid levels and the child being male led to an increased risk of the child being diagnosed with ASD (40). Another study involving maternal metabolite levels prepregnancy from blood samples stored from that time, found that mothers who had children with ASD showed differences in several metabolic pathways including bile acid pathways, glycosphingolipid synthesis, N-glycan and pyrimidine metabolism, and C21-steroid hormone biosynthesis and metabolism (41).…”
Section: Implication On Possible Role Of Nutritional/metabolic Statusmentioning
confidence: 99%